Educating sustainability through hackathons in the hospitality industry: a case study of Scandic hotels. Issue 2 (15th March 2021) - Phi, Giang Thi; Waldesten, Ted
ABSTRACT: Education for sustainability (EfS) in the hospitality sector is increasingly recognised as one of the driving forces for sustainable development. One way of fostering sustainability in the hospitality industry is through sustainability hackathons, which are intensive events focusing on "hacking" new sustainability ideas. This paper critically explores how the hospitality industry designs and executes sustainability hackathons within the context of EfS. An exploratory case study was conducted on the Scandic Hotels chain. Data utilised including both relevant reports and in-depth interviews with the highest level of management of Scandic. The execution of the sustainability hackathon illuminates how value-based education, creative problem-solving and co-opetition were critical aspects to foster EfS in the hospitality industry. Moreover, the hackathon facilitators, i.e. the hotels' General Managers, were found to play an essential part in shaping the sustainability education and the event's potential impacts. This paper contributes to expand knowledge on EfS offered by the hospitality industry (as opposed to EfS in formal educational institutions) and make practical recommendations on how sustainability hackathons could be better facilitated by hotel chains.